Teachers' enthusiasm and humor and its' lagged relationships with students' enjoyment and boredom - A latent trait-state-approach. (October 2022) - Bieg, Sonja; Dresel, Markus; Goetz, Thomas; Nett, Ulrike E.
Abstract: Following Pekrun's (2006) control-value theory of achievement emotions, we investigated carry-over effects and cross-lagged relationships between student-perceived teacher enthusiasm and humor and students' enjoyment and boredom both within and between university lectures. We used a latent state-trait approach to acknowledge the role of situational factors in this relationship. Data were collected from 559 university students (76% female, mean age 21.6 years) from seven different lecture courses. We assessed students' self-reported emotions and student-perceived teacher enthusiasm and content-related humor over a period of four lectures at three random points during each lecture course. The analyses revealed that all variables were influenced by previous measures within lectures; however, between lectures, only previous enjoyment and humor influenced the subsequent measure. When students experienced boredom, they perceived less teacher enthusiasm and humor. On the other hand, perceived teacher humor positively affected enjoyment within lectures. Highlights: Investigation of the variance components of students' enjoyment and boredom. Investigation of the variance components of perceived teacher enthusiasm and humor. Application of univariate and bivariate STARTS models. Examination of cross-lagged relations.